2012
DOI: 10.4103/0970-9371.101175
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated cryptococcosis presenting with generalized lymphadenopathy

Abstract: Cryptococcosis is a common opportunistic infection among immunocompromised individuals. Some of the commonly affected sites are respiratory and central nervous system. Lymph node is an unusual site of involvement which could mimic tuberculosis, as seen in our case. We report a 32-year-old male immunocompromised patient presenting with generalized lymphadenopathy who was clinically suspected to have tuberculous lymphadenitis. He was diagnosed to have disseminated cryptococcosis on fine needle aspiration cytolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…A similar proportion of disseminated cryptococcosis was found between those who had cryptococcosis diagnosis and received antifungal therapy, 20 (69.0%), and those with postmortem diagnosis, 11 (68.75%). The remaining 14 (31.1%) cases presented localized cryptococcal infection of meninges (11) or lung (three) ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar proportion of disseminated cryptococcosis was found between those who had cryptococcosis diagnosis and received antifungal therapy, 20 (69.0%), and those with postmortem diagnosis, 11 (68.75%). The remaining 14 (31.1%) cases presented localized cryptococcal infection of meninges (11) or lung (three) ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, meningeal and respiratory symptoms, fever, weight loss, anemia, lymph-node-enlargement, and hepatosplenomegaly are also observed. [11][12][13][14] The involvement of several organs such as adrenal gland, heart, skin, gut, thyroid gland, and prostate among others have been reported at necropsy studies carried out elsewhere. 6,15 Some reports have shown discrepancies between clinical and postmortem cryptococcosis diagnosis whereas others have pointed out some concerns with the decreasing rate of postmortem examination in teaching hospitals around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Other organs involved in order of decreasing frequency are skin, gastrointestinal tract and bone marrow, with the involvement of lymph nodes found in only few case reports 1 4. Philip et al 5 reported a case with generalised lymphadenopathy, hepatosplenomegaly and miliary patches on chest X-ray while Supparatpinyo6 reported that cryptococcal lymphadenitis presents with involvement of multiple sites. Our case was quite similar to his study, as our patient was also having disseminated cryptococcosis with lymphadenopathy of multiple sites (cervical, axillary, inguinal) along with hepatosplenomegaly and involvement of bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…[1234] C. neoformans commonly affects the lung, meninges, and skin. Lymph node is an unusual site of cryptococcal infection.…”
mentioning
confidence: 99%
“…Lymph node is an unusual site of cryptococcal infection. [1234] Diagnosis of cryptococcal lymphadenitis remains a potential challenge because the disease may be mild or subclinical with lack of characteristic clinical and radiological features. [5] Fine needle aspiration cytology (FNAC) is an easy, rapid, and reliable diagnostic method in cryptococcal lymphadenitis, which helps in the prompt initiation of treatment.…”
mentioning
confidence: 99%